Does financial inclusion affect non-performing loans and liquidity risk in the MENA region? - Abdelaziz Hakimi; Hichem Saidi; Lamia Adili (Economies, 2025)
Over the past decade, the debate on the microeconomic effects of financial inclusion has intensified, with a growing body of research exploring how access to financial services impacts banks' behaviors. Studying the effect of financial inclusion on bank risk is crucial because it helps understand how expanding access to financial services influences exposure to bank risks. This study explores the impact of financial inclusion on credit risk, measured by non-performing loans (NPLs), and liquidity risk measured by the loan-to-deposit (LTD) ratio in the Middle East and North Africa (MENA) region. The analysis is based on a sample of 74 banks observed between 2010 and 2021, and uses the System Generalized Method of Moments (SGMM). To conduct a comparative analysis, the whole sample is divided into two groups: the first includes GCC countries, while the second consists of non-Gulf Cooperation Council countries (NGCC). This sensitivity analysis was justified by several economic, financial, social, and regulatory differences between these two groups of countries. The findings reveal that across the MENA region and the two sub-regions, financial inclusion significantly reduces liquidity risk. However, it increases the level of NPLs in the Gulf Cooperation Council (GCC) countries. Furthermore, findings indicate that banks in the MENA region and the GCC countries benefit from an interaction between financial inclusion and liquidity since it significantly reduces the level of NPLs. Finally, the analysis shows that financial inclusion does not play a moderating role in the relationship between credit and liquidity risks in the NGCC countries.
Keywords: G21; G28; G32; 330; financial inclusion; credit risk; liquidity risk; MENA region; GCC; NGCC; SGMM